2020
DOI: 10.1101/2020.09.18.20197590
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

SARS-CoV-2 antigen and antibody prevalence among UK staff working with cancer patients during the COVID-19 pandemic

Abstract: Background International guidelines for testing potentially immunosuppressed cancer patients receiving non-surgical anticancer therapies for SARS-CoV-2 (COVID-19) are currently lacking. The value of routinely testing staff treating cancer patients is not known. Methods: Patient-facing oncology department staff at work during the COVID-19 pandemic consented to have a nasopharyngeal swab SARS-CoV-2 antigen test by polymerase chain reaction (PCR) and blood tests for SARS-CoV-2 antibody using a laboratory Lumin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Staff from RPH were recruited through staff email over the course of 2 months: 20 April 2020‐10 June 2020, as part of a prospective study to establish seroprevalence and immune correlates of protective immunity to SARS‐CoV‐2 (Ethics Approval: HRA IRAS: 96194 REC: 12/WA/0148). Staff from CUH and QEH were recruited through the COVID‐19 Serology in Oncology Staff (CSOS) study (Favara et al , 2021a; Favara et al , 2021b) with samples collected in June, July and December 2020 (Ethics approval: HRA IRAS: 284231). Samples were screened for SARS‐CoV‐2 N and S binding antibodies by Luminex assay as previously described (Kemp et al , 2021) and selected for further investigation based on selective binding profiles.…”
Section: Methodsmentioning
confidence: 99%
“…Staff from RPH were recruited through staff email over the course of 2 months: 20 April 2020‐10 June 2020, as part of a prospective study to establish seroprevalence and immune correlates of protective immunity to SARS‐CoV‐2 (Ethics Approval: HRA IRAS: 96194 REC: 12/WA/0148). Staff from CUH and QEH were recruited through the COVID‐19 Serology in Oncology Staff (CSOS) study (Favara et al , 2021a; Favara et al , 2021b) with samples collected in June, July and December 2020 (Ethics approval: HRA IRAS: 284231). Samples were screened for SARS‐CoV‐2 N and S binding antibodies by Luminex assay as previously described (Kemp et al , 2021) and selected for further investigation based on selective binding profiles.…”
Section: Methodsmentioning
confidence: 99%
“…This approach was used by many previous studies [ 11 , 13 , 15 , 25 ]. Participants who did not report any of the 13 symptoms were considered asymptomatic [ 28 , 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…Studies reporting associations between seroprevalence and self-reported symptoms for healthcare workers (HCWs) found that fever, malaise, and fatigue were especially common alongside anosmia and ageusia [ 25 , 26 ]. However, little is known about HCWs from oncology departments and cancer centers despite the fact that they have been a under major strain during the pandemic [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%